Outcome and toxicity of ifosfamide, carboplatin, and etoposide versus gemcitabine and vinorelbine regimen for pediatric patients with relapsed or refractory Hodgkin’s lymphoma - Mahdy, Ahmed; Hamoda, Asmaa; Zaher, Ahmed; Khorshed, Eman; Elwakeel, Madeha; Hassanein, Omneya; Sidhom, Iman (Frontiers in Oncology, 2023)
Background: Pediatric classical Hodgkin lymphoma (CHL) is a curable disease; however, the optimal salvage regimen is unclear for relapsed/refractory (R/R) disease. This study aimed to compare response rates, toxicity, event-free survival (EFS), and overall survival (OS) of Ifosfamide, Carboplatin, Etoposide (ICE) with Gemcitabine, Vinorelbine (GV) regimen after first-line ABVD (Doxorubicin, Bleomycin, Vinblastine, Dacarbazine) in pediatric patients with R/R CHL. Methods: This is a retrospective cohort study of 132 pediatric patients with R/R CHL treated from July 2012 to December 2020 with ICE (n=82) or GV (n=50). Results: The median age at relapse was 13.9 years and 68.2% were males. Rates of complete response, partial response, and progressive disease before consolidation were 50.6%, 3.7%, and 45.7% for ICE, 28.5%, 0%, and 71.5% for GV (P= 0.011). By multivariate analysis, regimen (P=0.002), time to relapse (P=0.0001), and B-symptoms (P=0.002) were independent factors to lower response rates. Hematological toxicity, electrolytes disturbance, hemorrhagic cystitis, infectious complications, and hospital admission for fever neutropenia were statistically significant higher for the ICE regimen. Treatment-related mortalities were 2.4% for ICE and 2% for GV (P=0.86). The 3-year EFS was 39.3%±11.4% for ICE and 24.9%±12.5% for GV (P=0.0001), while 3-year OS was 69.3%±10.6% and 74%±12.9% (P=0.3); respectively. By multivariate analysis, regimen (P=0.0001), time to relapse (P=0.011), B-symptoms (P=0.001), and leukocytosis (P=0.007), were significant for EFS, while anemia (P=0.008), and progressive disease on early response evaluation (P=0.022), were significant for OS. Conclusions: The ICE regimen had a better overall response rate and EFS, but higher toxicity, than GV, however, OS and mortality were similar